Some objective factors influencing delinquent behavior of regional youth in the 2000s - V. S. Yuzhaninov (Вестник университета)
Delinquent behavior and objective factors influencing it have been considered. It should be noted that crime is a complex phenomenon, which is influenced by many factors. Modern scientists combine these factors into two large groups such as subjective (or socio-cultural) and objective (or socio-economic). In order to study the latter and establish the existence of a relationship between them and youth crime, we have selected the most common criminal acts committed in the youth environment such as theft and robbery, as well as the most numerous crimes committed by young people against life and health such as infliction of minor and moderate harm to health. Among objective factors, we have chosen the indicators that can have the strongest impact on youth crime as a whole and on its individual categories such as average monthly accrued wages in the region, cash income per capita, and average per capita consumer spending. According to the conducted simple statistical analysis results, an inverse correlation between the number of criminals committing property crimes and the selected socio-economic factors has been revealed. Due to the use of a simple research method, it was not possible to establish any dependence of the number of young people committing crimes against property on the selected objective (socio-economic) factors.